2010
DOI: 10.1152/ajpendo.00746.2009
|View full text |Cite
|
Sign up to set email alerts
|

Secreted surfactant protein A from fetal membranes induces stress fibers in cultured human myometrial cells

Abstract: In the present study, we investigated the ability of human fetal membranes (amnion and choriodecidua) to regulate human maternal uterine cell functions through the secretion of surfactant protein (SP)-A and SP-D at the end of pregnancy. We detected the expression of both SP-A (SP-A1 and SP-A2) and SP-D by quantitative reverse transcription polymerase chain reaction. Immunohistochemistry revealed that human fetal membranes expressed both SP-A and SP-D. By Western blot analysis, we demonstrated that SP-A protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 40 publications
2
15
0
Order By: Relevance
“…The inclusion of so many of the significantly changing proteins (n = 11) in the actin/cytoskeleton-related protein group out of 20 significant changes between WT and KO indicates that SP-A has a profound influence on actin-related/cytoskeletal processes such as macrophage motility and phagocytosis, potentially explaining the susceptibility of the KO mice to injury or infection. In vitro studies have shown that an intact actin cytoskeleton, as assessed by the use of cytochalasin D, an actin depolymerizing agent, is required for certain SP-A-mediated processes [44] and in extrapulmonary tissues SP-A regulates F-actin filament organization [45]. Although given the importance of actin in cell motility, phagocytosis, and endocytosis, it is not surprising that changes in these proteins do occur, but the extent to which SP-A affects the content of so many actin/cytoskeletal-related proteins in vivo is remarkable.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The inclusion of so many of the significantly changing proteins (n = 11) in the actin/cytoskeleton-related protein group out of 20 significant changes between WT and KO indicates that SP-A has a profound influence on actin-related/cytoskeletal processes such as macrophage motility and phagocytosis, potentially explaining the susceptibility of the KO mice to injury or infection. In vitro studies have shown that an intact actin cytoskeleton, as assessed by the use of cytochalasin D, an actin depolymerizing agent, is required for certain SP-A-mediated processes [44] and in extrapulmonary tissues SP-A regulates F-actin filament organization [45]. Although given the importance of actin in cell motility, phagocytosis, and endocytosis, it is not surprising that changes in these proteins do occur, but the extent to which SP-A affects the content of so many actin/cytoskeletal-related proteins in vivo is remarkable.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, virtually nothing is known about the in vivo effect of SP-A on the alveolar macrophage proteome under basal or unstimulated conditions, with regards to whether and which groups of proteins SP-A may affect under such conditions. However, based on recent in vitro studies, in response to LPS [44] or in extrapulmonary tissues [45], it appears that the integrity of the cytoskeleton is required in order for SP-A-mediated processes to occur.…”
Section: Introductionmentioning
confidence: 99%
“…Expression of SP-A and SP-D has also been reported in extra pulmonary tissues such as brain, salivary glands, lachrymal glands, heart, trachea, kidney, pancreas, thymus, spleen, gall bladder, esophagus, small intestine, large intestine, testis, prostate and urinary tract (Madsen et al, 2003;Herías et al, 2007;Breuiller-Fouché et al, 2010;Nayak et al, 2012;Schicht et al, 2015). In addition, reproductive tissues have also been shown to express both SP-A and SP-D (Sati et al, 2009;Condon et al, 2004;Yadav et al, 2011).…”
Section: Introductionmentioning
confidence: 97%
“…Quantitative real-time RT-PCR demonstrated expression of SP-A1 mRNA, which was 17.4-fold higher in patients delivering preterm with chorioamniotis. Several studies have also established that SP-A is an important marker that increases during the intricate signaling that mediates parturition (Breuiller-Fouche et al, 2010; Chaiworapongsa et al, 2008; Garcia-Verdugo et al, 2010; Leong et al, 2008; Salminen et al, 2008; Snegovskikh et al, 2011; Yadav et al, 2011). Most recently, statistically significant delay in the time to parturition was evident in SP-A and D doubly deficient mice (Montalbano et al, 2013).…”
Section: Review Of the Localization And Known Functions Of Extra-pmentioning
confidence: 99%